The impact of advertising on women’s self-perception: a systematic review - Dai, Yao; Zhu, Zhixuan; Yuan Guo, Wu (Frontiers in Psychology, 2025)
This systematic review explores the multifaceted psychological impact of advertising on women’s self-perception, examining traditional advertising, femvertising, and the emerging effects of digital transformation. By synthesizing evidence from 95 peer-reviewed studies, this review examines the relationship between media portrayals of women and key psychological outcomes, including body image, self-esteem, self-objectification, and gender role attitudes. Our analysis reveals that traditional advertising, which often features idealized and stereotypical portrayals of femininity, continues to be associated with negative psychological outcomes such as increased body dissatisfaction and self-objectification. These effects appear to be intensifying in digital contexts, where exposure is more frequent and pervasive. Femvertising—advertising that aims to challenge gender stereotypes and empower women—shows promise in promoting positive psychological outcomes, but its effectiveness is contingent on perceived authenticity and individual viewer characteristics. The digital transformation of advertising has created new dynamics in how women encounter and process advertising messages, with social media platforms enabling both new forms of feminist messaging and new risks of superficial appropriation. Our findings suggest that understanding advertising’s impact requires consideration of platform-specific features, user characteristics, and content types. The review highlights the need for advertising practices that prioritize genuine representation and empowerment of women, while also addressing the unique challenges and opportunities presented by digital platforms. This work contributes to a deeper psychological understanding of advertising’s impact on women’s self-perception and calls for updated theoretical frameworks and practical approaches that can address both traditional and emerging forms of advertising exposure.